Dynamic Shear Failure Model for Ductile Materials - Partom, Yehuda (European Journal of Applied Sciences, 2022)
We propose a model for the shear failure of viscoplastic materials under dynamic loading. We use the overstress approach to dynamic plasticity, and include thermal softening, mechanical damage softening, strain hardening and pressure hardening. We demonstrate the model performance in torsion of a thin-walled tube. We introduce an initial yield stress reduction perturbation at the tube mid-section, and a shear band is formed there and then develops all the way to material failure. At the end we propose a scheme for applying our dynamic shear failure model to a computational cell of a macroscale hydrocode computation.